Bagian Hak Wasiat Wajibah Anak yang Beragama Non Muslim terhadap Harta Peninggalan Orang Tua yang Beragama Islam - Samriadin Samriadin (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Inheritance distribution in Islam is one of the legal aspects regulated in detail in the Qur'an, hadith, and fiqh. Islamic inheritance law aims to provide justice and order in the distribution of a person's inheritance after death. This discussion is not only limited to the rights and obligations of heirs, but also includes dispute resolution mechanisms in various social and cultural contexts. In practice, inheritance problems from Muslims also intersect with non-Muslims, which can give rise to different perceptions among heirs or children of heirs who are not included in the heir group but receive a mandatory will in accordance with the provisions of positive law in relation to the distribution of inheritance of Muslims. In this study, the problem raised is how is the distribution of inheritance to non-Muslim children who receive mandatory testamentary rights over the inheritance of their Muslim parents, a case study of the Tigaraksa Religious Court decision Number: 1657/Pdt.G/2020/PA.Tgrs dated November 25, 2020. The purpose of this study was to determine the distribution of inheritance to non-Muslim children who receive mandatory testamentary rights over the inheritance of their Muslim parents. The results of the study showed that even though they do not have the status of heirs, non-Muslim children of the testator receive a mandatory testamentary share from the inheritance of their deceased parents (Heir) which does not exceed the share of the smallest heir or is equal to the share of the inheritance of a daughter. The inheritance is reduced by the testator's debt and is then divided into two parts, part of which is the joint property of the Heir and his wife, then the inheritance rights and mandatory testamentary rights are divided.